Gustatory vocabulary in luxury food advertising (based on FORTNUM & MASON and FORMAN & FIELD websites and social media platforms) - Belova , Alla (Current issues of Ukrainian linguistics: theory and practice, 2023)
The article highlights gustatory lexicon usage in advertising top quality foods by the two famous British shops – Fortnum & Mason (F&M) and Forman & Field (F&F). Advertising luxury goods, including fine foods, requires elegant style, refined vocabulary, particular argumentation and persuasion strategies, the need to communicate taste and flavour parameters precisely and efficiently. Textual description of luxury foods was studied to reveal how gustatory modality is packaged in English on the shops' websites and social media platforms. Taste, smell, touch as sensory sensations attract a lot of attention lately in Sensory Linguistics, Culinary Linguistics, Cognitive Linguistics, Multimodality Studies and Discourse Analysis. The article deals with the sensory vocabulary of English, with language units used to express gustation, "taste" words combinability and frequency, and overlapping zones of gustatory modality and olfactory, tactile, audio modalities when these sensations impact flavour. The research proved that basic taste terms – taste, salty, bitter, sour – that are used for conceptualization and categorization of sensory sensations are seldom used in promotion of fine foods; "flavour" is obviously preferable to "taste"; one of the basic taste terms – "sweet" – enjoys high frequency. Advertising foods on websites is more detailed and saturated with gustatory terms in comparison with promotion of the assortment on Facebook and Twitter. The adjective "delicious" and its derivatives remain the most frequently used words to characterize high quality of the luxury foods and delicious taste indicators. F&M's gustatory lexicon turned out more diverse than F&F's. Source-based taste words are used to denote the ingredients that predetermine the flavour. Flavour of F&M's foods is conceptualized and emphasized through –ness nouns. Intensifiers – derivatives of taste words and non-taste words – accentuate the flavour parameters. English gustatory lexicon is extended considerably through 'non-taste' adjectives with the positive evaluative meaning. Though gustation and olfaction are considered to be interconnected when tasting and eating food, olfactory modality is rarely found in foods descriptions while texture and freshness of some foods become of special importance.
Keywords: advertising, gustatory lexicon, gustatory modality, sensory linguistics, culinary linguistics, olfactory.